The Role of Ambidextrous Leadership in Public Organizations in Palu City - Hattab, Syahruddin; Daswati, Daswati; Nawawi, Muh. Nawawi; Amalia, Nurul (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study addresses the growing need for effective leadership in public organizations, particularly in the context of complex and dynamic environments. Ambidextrous leadership, characterized by the ability to balance exploration and exploitation, is crucial in fostering innovation while maintaining operational efficiency. The research aims to explore the role of ambidextrous leadership in public organizations in Palu City, with a focus on its impact on innovation, employee work behavior, and organizational performance. Employing a qualitative research methodology, the study involves in-depth interviews with key stakeholders, including leaders, employees, and organizational experts. Data is analyzed using thematic analysis to identify key patterns and themes related to leadership practices, innovation processes, and performance outcomes. The findings reveal that ambidextrous leadership significantly contributes to the enhancement of both innovation and organizational performance. This study highlights the critical role of ambidextrous leadership in balancing innovation and efficiency within public organizations in Palu, emphasizing its importance in creating an environment conducive to both exploration and operational stability. However, while some progress has been made, the full integration of ambidextrous leadership faces challenges such as resource constraints, resistance to change, and rigid policies, necessitating effective conflict management and a collaborative approach for sustainable organizational performance.